A Distribution Line Protection Scheme for Network with Distributed Generation - Adrianti Adrianti; Edwindiansyah Asharry; Muhammad Nasir (JURNAL NASIONAL TEKNIK ELEKTRO, 2021)
Installation of distributed generations (DGs) can cause performance degradation of distribution lines protection. Therefore, the objective of this paper is to propose a protection scheme that can be a solution for this protection line degradation.. The proposed scheme consist of quadrilateral distance relays at upper stream of the lines and directional overcurrent relays at downstream of the lines. The performance of the scheme was tested using Digsilent Powerfactory simulation. The simulation was carried out for four fault types, 0 - 50 Ohms fault resistance and four network conditions/scenarios. The test system consist of three current source i.e. Grid, DG1 and DG2. Variation on-off state of the three current sources is applied in order to check the ability of the scheme to perform correctly for multiple network condition and possibility installation of new DG in the future. The results show that the scheme perform correctly for all bolted fault regardless of fault types, fault location and network scenarios. For three phase and two phase to ground faults the scheme perform correctly for all simulated fault resistance. However, for single line to ground faults and phase to phase faults, the scheme has limitation on maximum fault resistance that can result in correct operation. In general, the proposed scheme able to protect the distribution lines better than the scheme of previous research, but it has a slightly higher chance to perform unwanted operation.Keywords : Distribution line protection, distributed generation, quadrilateral distance relay, directional overcurrent relay